2013
DOI: 10.1093/jxb/ert074
|View full text |Cite
|
Sign up to set email alerts
|

Local inhibition of nitrogen fixation and nodule metabolism in drought-stressed soybean

Abstract: Drought stress is a major factor limiting symbiotic nitrogen fixation (NF) in soybean crop production. However, the regulatory mechanisms involved in this inhibition are still controversial. Soybean plants were symbiotically grown in a split-root system (SRS), which allowed for half of the root system to be irrigated at field capacity while the other half remained water deprived. NF declined in the water-deprived root system while nitrogenase activity was maintained at control values in the well-watered half. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
91
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 65 publications
9
91
1
3
Order By: Relevance
“…De acordo com Ferrari et al (2015), o estresse causado por deficit de água leva à ocorrência de plantas de soja pouco desenvolvidas, com pequena estatura e área foliar reduzida, pois uma das alterações provocadas pelo estresse hídrico é a redução do potencial hídrico foliar, que causa o fechamento estomático e, consequentemente, a diminuição das trocas gasosas e a inibição de vários processos bioquímicos e fisiológicos, como a fotossíntese, respiração, absorção de íons, metabolismo dos nutrientes, entre outros. Além disso, a irrigação incrementou a massa de matéria seca de nódulos (Tabela 2), pois a nodulação é influenciada pelo conteúdo de água no solo (Siczek & Lipiec, 2011), e a fixação biológica de N é um processo metabólico muito sensível ao deficit de água em plantas de soja (Gil-Quintana et al, 2013;King et al, 2014).…”
Section: -------------------------------(Cm)-------------------(g Porunclassified
“…De acordo com Ferrari et al (2015), o estresse causado por deficit de água leva à ocorrência de plantas de soja pouco desenvolvidas, com pequena estatura e área foliar reduzida, pois uma das alterações provocadas pelo estresse hídrico é a redução do potencial hídrico foliar, que causa o fechamento estomático e, consequentemente, a diminuição das trocas gasosas e a inibição de vários processos bioquímicos e fisiológicos, como a fotossíntese, respiração, absorção de íons, metabolismo dos nutrientes, entre outros. Além disso, a irrigação incrementou a massa de matéria seca de nódulos (Tabela 2), pois a nodulação é influenciada pelo conteúdo de água no solo (Siczek & Lipiec, 2011), e a fixação biológica de N é um processo metabólico muito sensível ao deficit de água em plantas de soja (Gil-Quintana et al, 2013;King et al, 2014).…”
Section: -------------------------------(Cm)-------------------(g Porunclassified
“…Intra-species variation in biological nitrogen fixation has been observed throughout the legume family [30,87] including within Glycine max (soybean) [88], Lablab purpureus [89], Vicia faba (faba bean) [90,91], Trifolium alexandrinum (bersem clover) [36,[92][93][94], Phaseolus vulgaris (common bean) [95,96], Pisum sativum (green pea) [97], V. unguiculata (cowpea) [98], and Vigna aconitifolia (mothbean) [93]. Optimizing biological nitrogen fixation involves the selection of not only the best legume genotype but also selecting the most optimal legume and rhizobia combination [30].…”
Section: Dry Season Wild Plants Can Be Optimized As Cover Crops Throumentioning
confidence: 99%
“…In soybean, the suppression of protein synthesis was previously reported in root including hypocotyl by flooding stress 42,43 . Furthermore, drought stress also led to suppression of protein synthesis in root tip 44,45 . In addition, the proteomic analysis of endoplasmic reticulum proteins of soybean root tip also indicated that protein synthesis was affected by flooding stress 8 .…”
Section: Transport and 60s Pre-ribosome Biogenesismentioning
confidence: 99%